Deep Desulphurization Study of Liquid Fuels Using Acid Treated Activated Charcoal as Adsorbent - Shah, Syed Sikandar [UNESP]; Ahmad, Imtiaz; Ahmad, Waqas; Ishaq, Muhammad; Khan, Hizbullah (American Chemical Society (ACS), 2017)
The current study addresses the improved desulphurization activity of activated charcoal modified by acetic acid treatment. The modified activated charcoal was investigated as an adsorbent for the elimination of sulfur compounds from the model oil (consisting of dibenzothiophene (DBT) dissolved in cyclohexane) as well as real oil samples including kerosene and diesel oil. In the case of model oil, about 99.5% of DBT was removed under conditions optimized in the laboratory, which included 15 mL feed (model oil) volume, 0.8 g of adsorbent, 60°C temperature, stirring speed of 100 rpm, and contact time of 1 h under neutral pH. In the case of real oil samples, i.e., kerosene and diesel oil, sulfur removal of 78.69% and 74.29% was attained under optimized conditions, respectively. Experimental results were interpreted through model adsorption isotherms, which indicated that the adsorption process is in close agreement with the Langmuir adsorption isotherm in comparison to the Freundlich adsorption isotherm. The spent adsorbents were regenerated to view their repeated use, simply by washing separately with organic solvents such as toluene, acetonitrile, methanol, and chloroform. Among these, toluene was found to be the best solvent for the regeneration of the spent adsorbents. The regenerated adsorbents were reused and regenerated for six consecutive regeneration cycles.